Variation Effect Of Fiber Composition And Direction TowardComposite Mechanical Properties, Fiberglass Fiber With Polister Matrix Material - Mainaki, Roberto Agus; , Ir. Pramuko Ilmu Purboputro, MT; , Wijianto, ST, M.Eng, Sc (2014)
With the development of technology, it is found, new technology in modification motorcycle body, so a lot of people utilize composite for making motorcycle body with the performance they want. It is easy to make body of motorcycle in willingness. There are three materials in the modifications motorcycle body (catalyst, resin and fiberglass). Fiberglass is a light material, and it is very strong. Though the character of its strength rather lowers that carbon fiber and less stiff, the material which is usually fragile, and the standard material is cheaper. Missal strength and weight character of body is also to make more than metal, and it is easy to make with the press. The purpose of the research is to know the strength of different fibers, from random fiber, woven fiber, and one direction fiber. Testing is done by differentiating three fibers (random fiber, woven fiber, and one direction fiber) with catalyst composite and the same resin. Every fiber tests with impact test that is based ASTM D - 256, bending test based on ASTM D - 790 and tensile test that is based on ASTM D - 638. The composition of a catalyst 4.76 % of a resin used, and use of composite volume faction 37.1 %. Analysis is done after getting result data of testing. The result from each testing has a different result. Numbers of height of impact test are gotten from one direction fiber 0.82 J/mm2, flexure stress is gotten from woven fiber 29.89 MPa, tensile strength is gotten from woven fiber 66 MPa, and elastic modulus from woven fiber 142.268 kg/mm2. The strength to hold is a strength and character as tenacity, strength, hardness etc, it can be considered by data which are gotten from the results of the test.